2022-RA-1271-ESGO Ultrasound guided biopsy, a useful tool in the management of primary advanced tuboovarian carcinoma. (20th October 2022) - Mascilini, Floriana; Quagliozzi, Lorena; Mirandola, Mariateresa; Moro, Francesca; D'Alessandris, Nicoletta; de Felice, Francesca; Testa, Antonia Carla; Scambia, Giovanni; Fagotti, Anna
Abstract : Introduction/Background: To assess the accuracy of pathological diagnosis at ultrasound (US)-guided biopsy versus surgery in patients with primary advanced tubo-ovarian carcinoma. Feasibility, adequacy, and safety of the procedure were also evaluated. Methodology: Consecutive women with pre-operative suspicious advanced tubo-ovarian carcinoma presenting at our hospital between July 2019 and September 2021 were enrolled. Feasibility was defined as the number of cases in which US-guided biopsy was possible according to tumour characteristics (morphology and site). Adequacy was defined as the possibility of a conclusive diagnosis in the sample collected. Safety was defined on the number of major complications. Results: 278 patients were eligible for the study; 158 were enrolled, while 120 were excluded due to logistic reasons or patient refusal ( figure 1 ). US-guided biopsy was unfeasible in 30 (19%) patients. The samples obtained in the remaining 128 cases were all adequate (100%), and no major complications were noted. 26 (20%) patients started neoadjuvant chemotherapy on the bases of the diagnosis obtained by US, whereas 102 (80%) patients underwent surgery. Accuracy of US-guided biopsy versus surgery was 94% (96/102), with 6 false negative cases at US (6%). Site (pre-vescical peritoneum) and size (< 8 mm) of the nodules resulted as major predictive factors for US-guided biopsy failure. US-guided biopsy correctly identified 86 primary invasive tubo-ovarian carcinomas and 10 metastatic tumours. Conclusion: US-guided biopsy is a feasible, safe, and accurate method to provide histologically diagnosis in suspicious advanced tubo-ovarian cancer patients.